Структура лексико-семантичного поля у межах художнього тексту - Holovashchenko, Yuliia (Рута, 2022)
The article is dedicated to the issue of a lexical-semantic field within an author’s literary text. A lexical-semantic field is viewed as a paradigmatic group of lexical units that are united in accordance with sematic affinity of lexical meanings. A lexical-semantic field is explained to possess a hierarchical structure, which allows to ensure a developed semantic picture of a certain conceptual field. Based on the novels of John Maxwell Coetzee, the structure of a lexical-semantic field is outlined. It encompasses semantic concretization of specific areas of individual author’s linguistic world picture.
Structure of lexico-semantic field in literary text
Keywords: Lexical semantic field; Literary text; Meaning; Sense